Influence of Ground Temperature on Shotcrete-to-Rock Adhesion in Tunnels - Limin Duan; Yuanhang Zhang; Jinxing Lai (Advances in Materials Science and Engineering)
Long and deep tunnels are increasingly designed and built worldwide, often in severe geothermal environments characterized by high temperature in the rocks. This issue cannot be ignored because high temperature definitely affects the strength of the adhesion between the concrete and the surrounding rocks, whatever the lining cast in place, segmental or sprayed using shotcrete. The causes of geothermal heat and the effect of the temperature on tunnel linings during and after their construction are recalled and discussed in this paper. Both temperature and humidity are shown to be the most relevant factors affecting adhesion strength, whose loss is related to the microdamage in the shotcrete layers closest to the rock. Possible ways to improve adhesion strength and to minimize the high-temperature detrimental effect are also presented and discussed.